Od algoritma do prava: Pravni, ekonomski in kulturni izzivi umetne inteligence (University of Maribor Press, 2025)
From Algorithm to Law: Legal, Economic and Cultural Challenges of Artificial Intelligence. Artificial intelligence is increasingly reshaping modern society and permeating nearly all areas of human activity – from law, economics, and education to media and culture. The scientific monograph From Algorithm to Law – Legal, Economic, and Cultural Challenges of Artificial Intelligence brings together contributions that focus on the challenges, opportunities, and consequences of AI implementation in today’s world. The monograph addresses AI’s impact on cultural heritage – such as digitalization and interpretation of sensory elements like scents – as well as economic aspects and a wide range of legal issues. These include labour relations, constitutional dilemmas, liability for damages, smart contracts, competition law, criminal law, and the use of AI in judicial proceedings. Special attention is given to intellectual property law, particularly the question of who holds rights to copyright-protected works, inventions, and product designs created by or with the assistance of artificial intelligence, including questions concerning the infringement. The monograph thus explores legal, economic, and cultural challenges posed by artificial intelligence and encourages reflection on the need for more comprehensive regulation and the responsible development of emerging technologies.